2022
DOI: 10.3390/nano12234247
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Modified Carbon Black on Nylon 6 Nonwoven Fabric and Performance as Adsorbent Material

Abstract: The number of chronic kidney disease (CKD) persons continues to rise in Mexico. They require renal replacement therapy, and in the absence of it, hemodialysis is the major option for their survival. The uremic toxins present in the blood are removed by hemodialysis, which involve membranes. In this study, nonwoven fabrics with modified carbon black nanoparticles in a matrix polymer of Nylon 6 were obtained and evaluated as an adsorbent material of uremic toxins. All nonwoven fabrics were characterized by FTIR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…Figure 6 b shows the inulin adsorption: after 210 min, the maximum adsorption capacity of 48% is reached for neat Nylon 6. This result is in agreement with Andrade et al [ 11 ]. Non-woven fabric Nylon 6/C20A 1.5% and Nylon 6/C20A 2% present similar behavior in the inulin adsorption process.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Figure 6 b shows the inulin adsorption: after 210 min, the maximum adsorption capacity of 48% is reached for neat Nylon 6. This result is in agreement with Andrade et al [ 11 ]. Non-woven fabric Nylon 6/C20A 1.5% and Nylon 6/C20A 2% present similar behavior in the inulin adsorption process.…”
Section: Resultssupporting
confidence: 94%
“…In the last study with carbon-based nanoparticles, the maximum adsorption efficiency was 80 to 95% for uremic toxins. This is because the surface area is greater and due to the chemical modification of the nanoparticles [ 11 ]. Andrade et al reported an adsorption efficiency for urea of 65% and 97% for methylene blue with the same modified nanoclays used in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multilayer graphene nanoplatelets (GNP) with a diameter of 2 µm, a thickness of 8 to 12 nm, and a purity of 97% (Cheap Tubes Inc., Cambridgeport, VT, USA) were used. The functionalization of the graphene nanoplatelets was obtained with 4-aminobutyric acid, following the method described in previous studies [ 88 ]. Functionalized graphene nanoplatelets (FGNP) contained a 34.5% modification with respect to non-functionalized GNPs.…”
Section: Methodsmentioning
confidence: 99%
“…The functionalization of the graphene nanoplatelets was obtained with 4-aminobutyric acid, following the method described in previous studies [88]. Functionalized graphene nanoplatelets (FGNP) contained a 34.5% modification with respect to non-functionalized GNPs.…”
Section: Treatmentsmentioning
confidence: 99%